2006
DOI: 10.1007/s11064-006-9188-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Neurons and Glia Following Neonatal Hypoxic-Ischemic Brain Injury in Rats

Abstract: Periventricular white matter injury in premature infants is linked to chronic neurological dysfunction. Periventricular white matter injury is caused by many mechanisms including hypoxia-ischemia (HI). Animal models of HI in the neonatal rodent brain can replicate some important features of periventricular white matter injury. Most rodent studies have focused upon early cellular and tissue events following unilateral neonatal HI that is elicited by unilateral carotid artery ligation and followed by timed expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
0
27
0
2
Order By: Relevance
“…This has been described previously and may be considered a result of plasticity of the brain (33). Plasticity is one of the most prominent features of the central nervous system, especially in the developing brain (34), and EPO has been reported to promote brain plasticity in both newborn and adult animal models of brain injury (29,35).…”
Section: Articlesmentioning
confidence: 68%
“…This has been described previously and may be considered a result of plasticity of the brain (33). Plasticity is one of the most prominent features of the central nervous system, especially in the developing brain (34), and EPO has been reported to promote brain plasticity in both newborn and adult animal models of brain injury (29,35).…”
Section: Articlesmentioning
confidence: 68%
“…In this study, we did not find improved brain volume by adding xenon to hypothermia as compared to hypothermia alone, however, we found a significant long-term functional improvement in the hypothermia-xenon group. The research group of F. Silverstein have demonstrated ongoing long lasting neuronal and glial degeneration and recovery in an ultrastructual study (29). Combining delayed HT and delayed xenon improved long-term functional outcome even without a corresponding increase in brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…Following H/I in the P9 mouse, several authors have reported decreased expression levels of myelin basic protein (MBP) and proteolipid protein (PLP), decreased neurofilament expression, and the presence of apoptotic cells in the corpus callosum within 24 to 72 hours after injury [66, 67]. White matter damage has been related to the loss of immature oligodendrocytes in the tracts as well as the loss of subventricular zone (SVZ) progenitors after H/I, inducing a depletion of oligodendrocyte precursors [68, 69]. …”
Section: Discussionmentioning
confidence: 99%